Great Britain, Blockades, and Neutral Rights: Royal Navy Operations during the Mexican- American War, 1846-1848 - Adamiak, Stanley (The Northern Mariner / Le marin du nord, 2021)
Although neutral during the Mexican American War (1846-8), Great Britain’s Royal Navy had to navigate the war’s naval component, particularly commerce raiding and blockades, as it sought to protect and promote trade and neutral rights. While able to use international pressure to limit privateering, handling the blockade proved more problematic. Although US policies largely mirrored British expectations in the Gulf of Mexico, along Mexico’s Pacific coast, inconsistent US Navy actions created tension. The professionalism of both American and British naval officers and a willingness of both governments to compromise effectively diffused any potential crises. Bien qu’elle soit restée neutre pendant la guerre américano-mexicaine (1846-1848), la Marine royale de la Grande-Bretagne a dû s’occuper de l’aspect naval de la guerre, en particulier les corsaires marchands et les blocus commerciaux, alors qu’elle cherchait à protéger et à promouvoir le commerce et la neutralité des droits. Pour limiter la course, la Marine pouvait recourir à des pressions exercées au niveau international, mais la gestion des blocus s’est révélée plus difficile. Bien que les politiques américaines aient reflété en grande partie les attentes britanniques dans le golfe du Mexique, les mesures incohérentes prises par la Marine américaine ont créé des tensions le long de la côte pacifique du Mexique. Le professionnalisme des officiers de marine américains et britanniques et la volonté des deux gouvernements de faire des compromis ont efficacement dissipé toute crise potentielle.